Effect of dietary cholesterol on ovarian development of Chinese mitten crabs (Eriocheir sinensis) - Guo, Huixing; Wang, Mangmang; Wang, Xi; Xiao, Kang; Huang, Yangyang; Hua, Haokun; Xiong, Wei; Liu, Wenbin; Abasubong, Kenneth Prudence; Qiang, Wei; Chi, Cheng; Jiang, Guangzhen (Frontiers in Marine Science, 2022)
Abstract: This study was conducted to evaluate the effect of cholesterol (CHO) on ovarian development of Eriocheir sinensis through a feeding trial. Crabs (average weight 43.35 ± 0.05 g) were randomly fed one of three diets: 0% CHO, 0.4% CHO and 1.6% CHO for 16 weeks. Results were indicated that the hepatosomatic index (HSI) and gonad index (GSI) of crabs fed with 0.4% CHO diet were significantly higher than those in the control group. (P < 0.05). Meanwhile, 0.4% CHO can significantly increase the gene expression of vtg and vgr in the ovary (P < 0.05), thus promoting the accumulation of Vtg. The protein expression of MEK1/2, ERK, p-ERK1/2, Cyclin B and CDC2 were significantly increased in 0.4% CHO group, therefore dietary CHO may promote oocyte maturation by activating MAPK signal pathway and cooperating with maturation promoting factor (MPF). Further exploration results show that 0.4% CHO can significantly upregulated the protein expression of STAR and SR-B1 to promote the transport of CHO to ovary, thereby providing sufficient substrates for estradiol (E2) synthesis. In addition, the results in vivo and in vitro were shown that CHO can regulate the activities of enzymes such as CYP11A1 and CYP19A1 through the cAMP-PKA-CREB/SF-1 signal pathway and then affects the level of E2 in the organism. In summary, supplementing the appropriate amount of CHO in the diet can improve the E2 level of the organism, thus increasing the accumulation of nutrients in the ovary, promoting the completion of meiosis, and finally achieving the purpose of promoting ovarian maturation.